Implementation Of Product Innovation And Market Orientation Strategies To Enhance Competitiveness - Saebah, Nur; Merthayasa, Alit; Suhardiman, Suhardiman (Jurnal Sosial Sains dan Komunikasi, 2024)
Strategy and innovation in business are activities that must be consistently carried out so that business people are still able to compete in an increasingly creative and complex industry. The accuracy of business people in understanding interactions within the scope of the market in question is a fundamental part in shaping the idea of strategy and innovation in business. The central role of product innovation strategies in efforts to improve competitiveness and good market orientation planning is the author's motive for conducting a study in the Bandung Regency was to validate the hypotheses regarding the impact of product innovation strategies and market orientation on competitive advantage in business markets. The utilized a qualitative approach and employed a survey research design for investigation. The population and sampling data used were 80 respondents. The findings indicated that the hypothesis regarding the effect of product innovation strategies exerts a substantial influence on improving quality of product competitiveness in the market and providing opportunities for excellence in market competition. While market orientation does not yield a notable impact.